Perancangan Instrumen Penilaian Kompetensi Pekerja Refinery dan Fraksinasi Plant 3 dan 4 PT. SMART, TBK - Harris Wibisono Hartanto (Jurnal Titra, 2019)
PT SMART Tbk. is a public company engaged in the processing of leading oil palm-based oil products in Indonesia. The company wants to do competency appraisal of workers in Refinery and Fractionation Plant 3 and 4 to find out how far are workers’ competencies that they have in doing their work. Competency appraisal is held by giving competency tests to workers. The purpose of this design is to make competency questions and instrumen for competency appraisal. The competency’s test is divided into five categories of competencies, namely quality, bleaching, deodorization, fractionation, and NSS process. The content of the question will be made based on taxonomy bloom concept. The instrument used for this competency is Microsoft office excel, while workers will work on the questions and answers in the program. Data processing is done directly on Microsoft office excel and analyzed the results of the appraisal and used of competency’s instrument. The result of competency appraisal showed that most of all workers have no balanced competencies. Score of quality and NSS’ process are the category of competencies with the lowest score. Workers provide feedback for the Competency instruments, so that development suggestions appear for the instrument and the Competence Process.